Mental health status of flood-affected adults in rural Tamil Nadu: A cross-sectional study - Venkatesh Ashok; K C Premarajan; Ravi Philip Rajkumar; Bijaya Nanda Naik (Wolters Kluwer Medknow Publications, 2019)
Objectives: The objective is to study the mental health status (in terms of posttraumatic stress disorder [PTSD]) of flood-affected adults aged 18 years and above residing in a rural village of Tamil Nadu affected by flood in December 2015. Methods: The study adopted a cross-sectional descriptive design. One adult member (age >18 years) preferably, head from each of the flood-affected households of Koonimedu village, Tamil Nadu, was included in the study. Participants were interviewed face to face 8 months after the occurrence of flood, and information on sociodemographic details and immediate effect of flood on health and property was obtained using semi-structured pretested questionnaire. Mental health and social support were assessed using the Impact of Event Scale-Revised (IES-R) and Crisis Support Scale, respectively. Mental health was expressed in terms of PTSD based on IES-R screening. Data analysis was done using statistical software. Results: The prevalence of PTSD as screened by IES-R among adults was found to be 51.3%. PTSD was found to be higher among females (56.7%) than males (43.3%). The elderly reported highest PTSD (63%). PTSD was found to be higher among participants who had received adequate social support. Conclusions: Even after 8 months of flood, the prevalence of screened PTSD was found to be very high and crisis social support low among individuals aged 18 years or above. Hence, mental health-care services including counseling support during and after the flood should be given priority by policy-maker.